Computer-Supported Instruction in Financial Statement Analysis. - Throckmorton, Jerry J.; Talbott, John (The Accounting Review, 1978)
ABSTRACT: Although financial statement analysis is a traditional classroom topic, the learning process in this area is often mitigated by simplistic examples which fail to deal with the vagaries of actual corporate reports. This paper proposes an alternative approach which requires students to examine real-world data, analyze the computer output generated and articulate their findings and conclusions in a written report.